REPRESENTASI PEREMPUAN DALAM KUMPULAN CERPEN “BH” KARYA EMHA AINUN NADJIB - Surya Dewi, I Desak Putu Kurnia; Sugiarica Joni, I Dewa Ayu; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2017)
Gender inequality is manifested in various forms, such as stereotyping or negative labelling. Stereotypes of women who are weak, emotional, identical to domestic sphere are considered normal and natural. This is constructed by the mass media, so it can affect the way the public view of women’s image. A collection of short stories “BH” by Emha Ainun Nadjib is one of the fiction books featuring women as the main subject. Of the twenty-three short stories that were published, there are two short stories that feature women who experience gender injustice, in between the short story titled Lelaki Ke-1000 di Ranjangku and Mimpi Istriku . The purpose of this research is to explain the representation of women in the collection of short stories “BH” by Emha Ainun Nadjib. This research used qualitative approach with critical discourse analysis method of Sara Mills. The results of this research are women represented in the position of second class and sexual objects in a short story titled Lelaki Ke-1000 di Ranjangku . Women are also represented easily emotional, irrational thinking, identical to domestic sphere, and positioned inferior in a short story titled Mimpi Istriku .   Keywords: collection of short stories “BH”,critical discourse analysis, Emha Ainun Nadjib, female representation, gender, Sara Mills, stereotype